A social support for housewives with HIV/AIDS through a peer support group - Sofro, Muchlis Achsan Udji; Hidayanti, Ema (Psikohumaniora: Jurnal Penelitian Psikologi, 2019)
Housewives with HIV/AIDS are faced with internal problems because the virus continues to invade their bodies and external problems such as caring for their husbands and children infected with HIV/AIDS, stigma and discrimination, maintaining family integrity and even taking responsibility for economic problems when the husband dies. They need social support. One of the most important sources of social support is peers, especially for those who have not done open status to the family. Peer support can be obtained through Peer Support Groups (KDS) through counseling, education, and information. This qualitative research using the methodology approach tries to explore the social support that is obtained by housewives with HIV/AIDS through peer support groups that they participate in General Hospital Dr. Kariadi Semarang. Research involving 15 informants shows that peer support groups can provide social support for them, including information support about the treatment and development of HIV/AIDS; emotional support, self-esteem support, and network support such as intensive communication and strong friendships; and real assistance: venture capital assistance, business skills, and assistance in accessing treatment